National cross-sectional study of the sociodemographic characteristics of Aotearoa New Zealand's regulated health workforce pre-registration students: A mirror on society? - Crampton, P.; Bagg, W.; Bristowe, Z.; Brunton, Paul; Curtis, E.; Hendry, C.; Kool, B.; Scarf, D.; Shaw, S.; Tukuitonga, C.; Williman, J.; Wilson, D. (2023)
Objectives To provide a sociodemographic profile of students enrolled in their first year of a health professional pre-registration programme offered within New Zealand (NZ) tertiary institutions. Design Observational, cross-sectional study. Data were sought from NZ tertiary education institutions for all eligible students accepted into the first ar of a health professional programme for the 5-year period 2016-2020 inclusive. Variables of interest: gender, citizenship, ethnicity, rural classification, socioeconomic deprivation, school type and school socioeconomic scores. Analyses were carried out using the R statistics software. Setting Aotearoa NZ. Participants All students (domestic and international) accepted into the first ar of a health professional programme leading to registration under the Health Practitioners Competence Assurance Act 2003. Results NZ's health workforce pre-registration students do not reflect the diverse communities they will serve in several important dimensions. There is a systematic under-representation of students who identify as Māori and Pacific, and students who come from low socioeconomic and rural backgrounds. The enrolment rate for Māori students is about 99 per 100 000 eligible population and for some Pacific ethnic groups is lower still, compared with 152 per 100 000 for NZ European students. The unadjusted rate ratio for enrolment for both Māori students and Pacific students versus Other' students is approximately 0.7. Conclusions We recommend that: (1) there should be a nationally coordinated system for collecting and reporting on the sociodemographic characteristics of the health workforce pre-registration; (2) mechanisms be developed to allow the agencies that fund tertiary education to base their funding decisions directly on the projected health workforce needs of the health system and (3) tertiary education funding decisions be based on Te Tiriti o Waitangi (the foundational constitutional agreement between the Indigenous people, Māori and the British Crown signed in 1840) and have a strong pro-equity focus.